Perancangan dan pengembangan produk ban hemat bahan bakar, aman dan nyaman dengan pendekatan Quality Function Deployment - Ayu Puspa Wirani; Aris Trimarjoko; Humiras Hardi Purba (Universitas Mercu Buana, 2019)
Product development by integrating consumer needs, technical capabilities and resources will enhance industrial competitiveness in era of globalization. Theme of this study is application of Quality Function Deployment (QFD) to develop design of tire products with consider fuel-efficient, safe and comfortable using. Based on primary data through questionnaires, there are 9 attributes that are desirable for consumers. In addition, through the brainstorming method, obtained 10 attributes that become technical specifications that can be developed into the product design. By arranging House of Quality (HOQ), the priority attributes of product design and development are light tires (20%), thin dimension (18%), synthetic rubber (14%), soft compounds (13%) and Smooth grip (11%).